Ownership and capital structure of Pakistani non-financial firms - Khan Shoaib; Suzuki Yasushi (e-Finanse: Financial Internet Quarterly, 2016)
Existing literature has not yet defined a clear-cut relationship between ownership structure and capital structure. This study aims to contribute to this controversial argument by examining the impact of internal (managerial) ownership and external ownership on financing preferences using the case of non-financial firms listed on Karachi stock exchange during the period of 2008-2012. Our results suggest that the external ownership has a significant effect on capital structure in accordance with the presence of blockholders. In contrast, the internal ownership has a complicated effect; it shows significant positive and negative relationship to leverage at lower and certain higher proportion of managerial shareholding respectively. Besides, the combined analyses suggest that the presence of blockholders negates the impact of managerial ownership on capital structure. This implies that the presence of large and dominant shareholders in Pakistani firms may have caused a bias for debt financing to protect their voting power and returns.
Keywords: G32; C51; 330; capital structure; ownership structure; shareholders; Pakistan